Sudden cardiac death and coronary artery anomalies in the athletes: A narrative review - Bianco, R.; Annarumma, G.; Cocola, A. C.; Sirico, F.; Romano, V. (Journal of Human Sport & Exercise, 2021)
Sudden cardiac death (SCD) in the athletes is an unexpected dramatic event. The mechanism underneath SCD is often represented by a ventricular tachyarrhythmia arising as complication of a broad spectrum of cardiovascular diseases, with a silent clinical course. Therefore, SCD often represents the onset manifestation of an underlying heart disease. To prevent SCD in the athletes, several international guidelines proposed pre-participation screening protocols to identify high-risk subjects. Behind atherosclerotic diseases, other structural or functional conditions have been related to SCD, such as hypertrophic cardiomyopathy, QT-long syndrome, arrhythmogenic right ventricular dysplasia, and others. Among these, the coronary artery anomalies represent almost the 20% of all cases. The coronary artery anomalies can be classified into anomalies of origin, course and termination and can be isolated or associated with other congenital cardiac defects. Some of them are rarely symptomatic. Others could impair heart function and determine SCD. Some others determine secondary cardiovascular diseases such as increased risk of endocarditis, secondary aortic valve diseases, myocardial ischemia, and others. Innovative diagnostic and therapeutic options allowed to recognize the different coronary artery anomalies, preventing SCD in athletes. The aim of this review was to analyse coronary artery anomalies to understand their implications in SCD in athletes.